1996
DOI: 10.3386/w5630
|View full text |Cite
|
Sign up to set email alerts
|

Borrowing Constraints and the Tenure Choice of Young Households

Abstract: In this paper we analyze the factors that affect the tenure choice of young adults, highlighting the impact of mortgage lender imposed borrowing constraints.The data set is a panel of youth age 20-33 for the years 1985-90. Our methods differ from most prior studies in many ways including consideration of possible sample selection bias, a richer model of the stochastic error structure, better measurement of which households are bound by borrowing constraints, and a fuller consideration of the endogeneity of wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 21 publications
6
139
0
Order By: Relevance
“…The negative relationship between household's credit quality constraints and the propensity to own is also well documented in the empirical literature (e.g. Linneman and Wachter 1989, Haurin et al 1997, Quercia et al 2003, and Barakova et al 2003 in the US, or Bourassa 1995, in Australia) 1 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The negative relationship between household's credit quality constraints and the propensity to own is also well documented in the empirical literature (e.g. Linneman and Wachter 1989, Haurin et al 1997, Quercia et al 2003, and Barakova et al 2003 in the US, or Bourassa 1995, in Australia) 1 .…”
Section: Introductionmentioning
confidence: 91%
“…Linneman and Wachter 1989, Bourassa 1995, Haurin et al 1997, and Barakova et al 2003. However, the traditional estimation of a univariate probit model will provide an inconsistent estimation for β, γ, and δ if the error term in a choice equation where CC i is endogenous is correlated with ε i (see Woolbridge 2002, Ch.…”
Section: Econometric Modelmentioning
confidence: 99%
“…Other control variables comprise of demographic, financial, and socioeconomic characteristics measured in 1994. Among the control variables, age is included because of its association with financial asset holdings in prior literature (Haurin, Hendershott, and Wachter 1996). Prior research has shown that Whites were more likely than minorities to hold high-risk and high-return assets (Keister 2000).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Other studies have consistently found that wealth and to a lesser extent credit constraints are more important than income constraints in limiting access to homeownership (eg. Barakova, Bostic, Calem, and Wachter 2003); others also point to the cost of owning relative to renting as a significant determinant (Haurin, Hendershott and Wachter 1997).…”
Section: Previous Researchmentioning
confidence: 99%